2016
DOI: 10.1590/1413-812320152111.19812015
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da compreensão da farmacoterapia entre idosos atendidos na Atenção Primária à Saúde de Belo Horizonte, MG, Brasil

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
35

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(59 citation statements)
references
References 33 publications
2
22
0
35
Order By: Relevance
“…There was a prevalence of incomes of between one and three minimum wages (MWs) among users of both health service providers, characterizing a low income population faced with increasing health costs arising from the ageing process and the increased occurrence of chronic diseases, as is the case in Brazil. For SUS users, this data is similar to that found in specialized literature 17 .…”
Section: Discussionsupporting
confidence: 87%
“…There was a prevalence of incomes of between one and three minimum wages (MWs) among users of both health service providers, characterizing a low income population faced with increasing health costs arising from the ageing process and the increased occurrence of chronic diseases, as is the case in Brazil. For SUS users, this data is similar to that found in specialized literature 17 .…”
Section: Discussionsupporting
confidence: 87%
“…Among the 227 elderly people interviewed, 51.1% presented insufficient understanding regarding medication, and the authors concluded that it is extremely necessary to plan strategies to increase the quality of the information and orientation given to the elderly person in order to ensure adherence and, consequently, compliance. 33 It is pertinent to highlight a study in which the participants highlighted several difficulties in the consultations that negatively impacted on their health experiences and the conditions to adopt healthy behaviours such as; communication difficulties, dialogue and information exchange FHL plays an important role in the health promotion of populations, and is intrinsically associated with health information and the health behaviour of users. This scenario refers to the importance of understanding the need for continuous monitoring of this public in order to achieve satisfactory health outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…When making a comparison with previous studies carried out over the last 17 years, 15,17,18 with patients on continuous use of medications, at different times, it was noticed that the CML patients of the HEMOAM Foundation, in relation to the knowledge variables about the use, duration and purpose of treatment, knew more about the pharmacotherapy.…”
Section: Rbfhss Revista Brasileira De Farmácia Hospitalar E Serviços mentioning
confidence: 95%